Effects of lovastatin and dietary cholesterol on bile acid kinetics and bile lipid composition in healthy male subjects - Duane, W C (Journal of lipid research, 1994)
We measured bile acid kinetics and bile lipids in 12 human subjects on a metabolic ward in four randomly allocated, 6-7 week periods: 1) lovastatin (40 mg b.i.d) + low cholesterol diet (mean 246 mg/day); 2) lovastatin+high cholesterol diet (mean 1071 mg/day); 3) low cholesterol diet alone; and 4) high cholesterol diet alone. Lovastatin did not significantly alter fractional turnover, synthesis, absorption, enterohepatic cycling, or pool sizes of bile acid measured by the Lindstedt method. The high cholesterol diet increased fractional turnover and synthesis rate of cholic acid, but not chenodeoxycholic acid, without altering pool size of either bile acid. The high cholesterol diet decreased bile acid absorption, but only during lovastatin treatment, suggesting the possibility of a “cholestyramine-like” effect of dietary cholesterol, appreciable at least when biliary cholesterol secretion is reduced by lovastatin. As in previous studies, lovastatin markedly lowered saturation index of gallbladder bile. Increased cholesterol consumption did not significantly alter cholesterol saturation index, suggesting that dietary cholesterol may not be a major factor in cholesterol gallstone pathogenesis.